2019
DOI: 10.4274/jcrpe.galenos.2018.2018.0221
|View full text |Cite
|
Sign up to set email alerts
|

Urine Levels of Matrix Metalloproteinases and Tissue Inhibitor of Metalloproteinases in Children with Type 1 Diabetes Mellitus

Abstract: Objective: Histopathological changes in the kidney in type 1 diabetes mellitus (T1DM) begin before detection of microalbuminuria. Therefore, there is interest in finding a better biomarker for the early detection of diabetic kidney injury. The aim of this present study was to determine whether urinary indicators of fibrosis are detectable early in the development of T1DM in children and if they may predict progressive renal injury. Methods: Urinary matrix metalloprotein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…MMP-9 activity has been associated with resistant albuminuria, both in a diabetic rat model and in diabetes patients [ 30 ]. Similar to our findings one previous study showed low levels of urinary MMP-9 in type 1 diabetes pediatric patients without microalbuminuria [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…MMP-9 activity has been associated with resistant albuminuria, both in a diabetic rat model and in diabetes patients [ 30 ]. Similar to our findings one previous study showed low levels of urinary MMP-9 in type 1 diabetes pediatric patients without microalbuminuria [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…Considering children with nephrotic syndrome displayed a higher level of MMP-1, -2, and -9, these MMPs have the potential to act as biomarkers for this disease [176]. However, one recent study has presented that the diabetic children urinary fibrosis biomarkers (levels of MMP-2, MMP-9, and TGF-β) versus the control group showed no significant difference [175]. Therefore, the role of MMPs in DKD is not yet fully understood.…”
Section: Mps In Fibrosis and Other Diseasesmentioning
confidence: 99%
“…This eventually leads to sclerosis and tubulointerstitial fibrosis, the hallmark of DKD pathogenesis [174]. Besides the major players, MMP-2 and MMP-9, TGF-β1 is recognized as a key factor that takes parts in the nephrotic fibrosis [175]. Considering children with nephrotic syndrome displayed a higher level of MMP-1, -2, and -9, these MMPs have the potential to act as biomarkers for this disease [176].…”
Section: Mps In Fibrosis and Other Diseasesmentioning
confidence: 99%